Addressing grammatical doubts among Orientalists - Bashn, Bushra; Hassan, Hassan (Al-Adab Journal, 2025)
This research deals with the claims of Orientalists about the issue of syntax in the Arabic language, which is one of the most prominent linguistic issues in the Arab heritage. The research focuses on analyzing the claims made by Orientalists about syntax, such as describing it as rigid and complex, and claiming that it constitutes an obstacle to learning and spreading the Arabic language.The research is divided into three main demandsThe first demand: The concept of syntax and its importance, where it sheds light on syntax as an aspect of linguistic precision in Arabic, and its role in controlling meaning and avoiding ambiguity in written and spoken texts.The second demand: About the claims of Orientalists about syntax, the demand reviews the most prominent claims of Orientalists, such as saying that syntax is an unnatural phenomenon, or that it is a late grammatical invention, or that the Arabic language can be understood and used without it.The third requirement: Scientific criticism of these allegations, as the research presents scientific responses based on heritage sources and modern studies to refute these allegations, while explaining the importance of syntax in preserving the identity of the Arabic language and its flexibility in expression.The research concludes that syntax is not just a formal system of the language, but rather represents a cultural and linguistic depth that reflects the flexibility of Arabic and its ability to adapt to the developments of time, and that the allegations of orientalists are mostly based on misunderstanding or cultural and linguistic bias. In addition, it confirms linguistic rules that prevent confusion and remove ambiguity to a large extent.